Benthic Bacterial Community Composition in the Oligohaline-Marine Transition of Surface Sediments in the Baltic Sea Based on rRNA Analysis - Klier, Julia; Dellwig, Olaf; Leipe, Thomas; Jürgens, Klaus; Herlemann, Daniel P. R. (Frontiers in Microbiology, 2018)
Salinity has a strong impact on bacterial community composition such that freshwater bacterial communities are very different from those in seawater. By contrast, little is known about the composition and diversity of the bacterial community in the sediments (bacteriobenthos) at the freshwater-seawater transition (mesohaline conditions). In this study, partial 16S-rRNA sequences were used to investigate the bacterial community at five stations, representing almost freshwater (oligohaline) to marine conditions, in the Baltic Sea. Samples were obtained from the silty, top-layer (0–2.5 cm) sediments with mostly oxygenated conditions. The long water residence time characteristic of the Baltic Sea, was predicted to enable the development of autochthonous bacteriobenthos at mesohaline conditions. Our results showed that, similar to the water column, salinity is a major factor in structuring the bacteriobenthos and that there is no loss of bacterial richness at intermediate salinities. The bacterial communities of marine, mesohaline, and oligohaline sediments differed in terms of the relative rRNA abundances of the major bacterial phyla/classes. At mesohaline conditions typical marine and oligohaline operational taxonomic units (OTUs) were abundant. Putative unique OTUs in mesohaline sediments were present only at low abundances, suggesting that the mesohaline environment consists mainly of marine and oligohaline bacteria with a broad salinity tolerance. Our study provides a first overview of the diversity patterns and composition of bacteria in the sediments along the Baltic Sea salinity gradient as well as new insights into the bacteriobenthos at mesohaline conditions.